2013
DOI: 10.1097/ccm.0b013e31828e969f
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin Versus C-Reactive Protein for Guiding Antibiotic Therapy in Sepsis

Abstract: C-reactive protein was as useful as procalcitonin in reducing antibiotic use in a predominantly medical population of septic patients, causing no apparent harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(147 citation statements)
references
References 38 publications
5
138
0
4
Order By: Relevance
“…We referred to 9 RCT reports during our meta‐analysis on this topic 78, 79, 80, 81, 82, 83, 84, 85, 86. No significant differences were observed between the intervention and control groups with respect to ICU stay time, hospitalization period, 60‐day mortality rate, and 90‐day mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…We referred to 9 RCT reports during our meta‐analysis on this topic 78, 79, 80, 81, 82, 83, 84, 85, 86. No significant differences were observed between the intervention and control groups with respect to ICU stay time, hospitalization period, 60‐day mortality rate, and 90‐day mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…In a French study (25) on non-surgical patients with suspected bacterial infection (73% with a respiratory infection) in seven ICUs, PCT-guided treatment initiation and discontinuation provided 23% more antibiotic free days compared to the control group (25). On the other hand, in a RCT in two Brazilian ICUs, a CRP-based algorithm was compared to a PCT-based algorithm in patients with severe sepsis and septic shock and CRP-based algorithm was found to have similar success (26). In our study, we observed that there is a moderate correlation between PCT versus SOFA and CRP versus SOFA at the antibiotic change day.…”
Section: Characteristics N=176mentioning
confidence: 97%
“…In fulminant disease courses, the CRP induction time (response-HT after stimulus 6-10 h, relative increase 10-100-fold) means that septic shock can already be present before laboratory analysis detects an increase in the CRP value. CRP is, however, of value for evaluation of disease course and monitoring of treatment efficiency [59,67]. Persistent increases in CRP level or a secondary increase in plasma concentration in patients on anti-infective therapy may indicate inadequate control of the infection (e. g., infectious complications, secondary infections, polymicrobial infections, MDR pathogens, ineffective antibiotic, inadequate antibiotic dosage; [59]).…”
Section: C-reactive Proteinmentioning
confidence: 99%